Y=mx+b m=-3/4 (1,3)
3=-3/4(1)+b
3=-3/4+b
b=3 3/4
y=-3/4+3 3 3/4
If we write out the expression √4√6/√3√2, then we get the solution to the surd as 2.
<h3>What is a surd?</h3>
A surd is an irrational number which is often shown as a square root. In this case, we have the value; √4√6/√3√2.
This is the same as; 2√6/√6. This now implies that we can cancel out the surd form which is shown as √6 hence the result of the expression is 2.
Learn more about surd:brainly.com/question/24700530
#SPJ4
Answer:
- equation: y = x+3
- inequality: y < x+3
Step-by-step explanation:
The slope of the line is 1 unit of rise for 1 unit of run, so ...
m = rise/run = 1/1 = 1
The y-intercept is 3 grid lines above the x-axis, so is (0, 3).
Then the equation of the line is ...
y = 1x +3
The inequality has that line as a boundary, but the y-values on the line are not part of the solution space. Only y-values below the line (less than those on the line) are in the solution. The inequality is ...
y < x +3
the answer is c because 4(4)+4(5)=36 and 2(4)^2=16 that 36-16=20 and mn (4*5)=20 so that gives you answer c